Опрацювання результатів вимірювання при відхиленні їх статистичних властивостей від типових - Бубела, Іванна Василівна (Національний університет "Львівська політехніка", 2016)
Дисертаційна робота присвячена створенню й дослідженню нової методики визначення непевності результатів вимірювань, якими є екстремальні (мінімальне чи максимальне) спостереження, а також опрацюванню простої і ефективної методики опрацювання спостережень з відмінними від нормального розподілами, що призведе до покращення якості виробництва продукції. Запропонована методика оцінювання непевності екстремального результату вимірювання ґрунтується на попередньому обчисленні теоретичних параметрів першої чи останньої порядкових статистик, а також експериментальних характеристиках (середнього значення та стандартного відхилення) зареєстрованих спостережень. Здійснено дослідження впливу інструментальної складової (систематичних та випадкових впливів) на непевність екстремального спостереження. Запропоновану методику застосовано до опрацювання результатів експериментальних досліджень під час контролю якості пластмасових труб на виробництві. Для опрацювання спостережень з розподілами, які істотно відрізняються від нормального, опрацьовано модифікований метод порядкових статистик, який ґрунтується на їх асимптотичних властивостях і який у практичній реалізації є простим, швидким та достатньо точним. Основні наукові результати мають як теоретичне, так і практичне значення та можуть знайти застосування при опрацюванні результатів вимірювань під час контролю параметрів якості продукції та виробів в промисловості, сільському господарстві та медицині. Диссертационная работа посвящена созданию и исследованию новой методики определения неопределенности результатов измерений, которыми являются экстремальные (минимальное или максимальное) наблюдения, а также разработке простой и эффективной методики обработки результатов наблюдений с отличными от нормального распределениями, что приведет к улучшению качества производства продукции. Предложенная методика оценки неопределенности экстремального результата измерения основывается на предварительных расчетах теоретических параметров первой или последней порядковых статистик, а также экспериментальных характеристиках (среднего значения и стандартного отклонения) зарегистрированных наблюдений. Проведено исследование влияния инструментальной составляющей (систематических и случайных воздействий) на неопределенность экстремального наблюдения. Предложенную методику применено к обработке результатов экспериментальных исследований при контроле качества пластмассовых труб на производстве. Для обработки наблюдений с распределениями, которые существенно отличаются от нормального, разработан модифицированный метод порядковых статистик, основанный на их асимптотических свойствах и который в практической реализации является простым, быстрым и достаточно точным. Основные научные результаты имеют как теоретическое, так и практическое значение и могут найти применение при обработке результатов измерений во время контроля параметров качества продукции и изделий в промышленности, сельском хозяйстве и медицине. The thesis is devoted to solving of important applied scientific task of is creation and research of new procedure for the determination of the uncertainty of measurement results when is extreme (minimal or maximal) value of observations аs well as simple and effective procedures of the processing the results of observations, with other than normal distributions with the aim of determination of the best (with the smallest standard uncertainty) evaluations of the measurement results, that will improved of quality of production of goods in accordance to the predictable necessities of consumers. The existing methods of processing uncertainty the of observations results are analyzed, in particular the order statistics method and also processing problems are set when results of the control measurements are extreme observations and their uncertainty must be determined. The nonstandard statistical method for evaluating uncertainty, when a minimal (extreme) observation is a result the measurement (or testing) and a number of observations is significantly limited: n = 3…10 and if the observations probability density function (PDF) differs from a normal distribution is proposed and analyzed. This method is based on some properties of order statistics. As example from the practice this method is used to evaluate the uncertainty of a percent elongation and tensile strength in testing plastic products. The accuracy of obtained theoretical and experimental results is also investigated by Monte Carlo simulation. Proposed method can be used to uncertainty evaluation of another quantities, when the minimal (or maximal) value of several normally distributed random observations is a result of measurement. As an example from practice this method is used to evaluate the uncertainty of investigations of mechanical properties when testing products (measurement results in a minimal value of observations) and in investigations of quantity a number of harmful elements in food industry products (measurement results in a maximal value of observations). The modified method based on order statistics for processing of the random observations with so called Flatten Gaussian distribution that is a convolution of rectangular and normal distributions is proposed. Proposed method in practical realization is simple, fast and enough accurate. This method is based on comparison of the input observations with a set of so called reference observations and provides automatic selection of the best (with the minimal standard uncertainty) location and scale parameters of the input observations. This method gives a smaller standard uncertainty of a location parameter compared to a standard uncertainty of a mean value. The efficiency of the method increases with the increase content of the uniform component. The implementation of the proposed method does not require complicated calculations and based on an analytical expression of a normalized Flatten Gaussian density distribution. Research results, obtained by Monte Carlo method, have confirmed the effectiveness of proposed method. Basic scientific results have both theoretical and practical value and can be used in the processing of measurement results during control of parameters of quality of products and products in industry, agriculture and medicine.
Обработка результатов измерения при отклонении их статистических свойств от типичных
Processing of measurement results by deviation of their statistics properties from typical
Keywords: вимірювання; розподіл; непевність результату; методика; екстремальні значення; мінімальне значення спостережень; максимальне значення спостережень; відносне видовження; межа плинності; контроль якості пластмасових труб; метод порядкових статистик; коваріаційна матриця; плоско-нормальний розподіл; метод Монте-Карло; измерения; распределение; неопределенность результата; методика; экстремальные значения; минимальное значение наблюдений; максимальное значение наблюдений; относительное удлинение; граница текучести; контроль качества пластмассовых труб; метод порядковых статистик; ковариационная матрица; плоско-нормальное распределение; метод Монте-Карло; measurement; distribution; uncertainty of result; procedure; extreme values; minimal value of observations; maximal value of observations; percent elongation; tensile strength; quality control of plastic tubes; order statistics method; covariance matrix; Flatten-Gaussian distribution; Monte Carlo method